Morphological Retrospective Study of Peritoneal Biopsies from Patients with Encapsulating Peritoneal Sclerosis: Underestimated Role of Adipocytes as New Fibroblasts Lineage? - Monika Tooulou; Pieter Demetter; Anwar Hamade; Caroline Keyzer; Joëlle L. Nortier; Agnieszka A. Pozdzik (International Journal of Nephrology)
Background. Encapsulating peritoneal sclerosis (EPS) is a rare but serious complication of peritoneal dialysis (PD). Besides the endothelial-to-mesenchymal transition (EMT), recently peritoneal adipocytes emerged as a potential source of fibrosis. We performed immunohistochemistry to approach EMT and to localize peritoneal adipocytes in peritoneal biopsies from PD-related EPS patients. Material and Methods. We investigated tissue expression of podoplanin, cytokeratin AE1/AE3 (mesothelium), calretinin (adipocytes), alpha-smooth muscle actin [α-SMA] (mesenchymal cells), interstitial mononuclear cell inflammation, and neoangiogenesis (CD3, CD4, CD8, CD20, CD68, and CD31 immunostainings, resp.). Results. Three patients (1 man/2 women; 17, 64, and 39 years old, resp.) developed EPS after 21, 90, and 164 months of PD therapy. In patients with EPS, we observed (1) loss of AE1/AE3 cytokeratin+ mesothelial cells without any evidence of migration into the interstitium, (2) disappearance of adipose tissue, (3) diffuse infiltration of calretinin+ cells in the areas of submesothelial fibrosis with a huge number of α-SMA and calretinin+ fusiform cells, and (4) increased vascular density. Conclusion. We report that the involvement of EMT in peritoneal fibrosis is difficult to demonstrate and that the calretinin+ adipocytes might be an underestimated component and a new source of myofibroblasts in peritoneal remodeling during PD-related EPS.